Peran Guru dalam Menumbuhkan Minat Membaca dan Menulis Braille pada Siswa Tunanetra - Nur Rahayu Setyawati; Mulyadi (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2021)
This study aims to describe the teacher's role in fostering interest in reading and writing braille for blind students at Cerme Gresik State Elementary School. This study uses a qualitative research method with a case study approach. Data observation techniques with observation, interviews, and documentation. Data analysis technique using Miles and Huberman. Test the validity of the data by triangulation and adequacy of references. The results showed that in learning to read and write braille the teacher made plans by involving students in CSOM activities, training children's motor and touch, introducing children to braille, preparing lesson plans, doing literacy, and providing motivation. The implementation of reading and writing learning uses the lecture, discussion, question and answer method, BCM, drill, sorogan and assignments. Evaluate directly learning to read and write.